The Relationship of Self-Control and Religious Orientation to Attitude toward Pre-marital Relations - Rasool Barzegar khezri; Anahita Khodabakhshi -Koolaee (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Today premarital friendships between boys and girls is one of the most important cultural and social issues which can greatly affect the health of young people. The role of religion and self-control in mental health is of particular significance. Given the importance of these issues, this study aimed to determine the relationship of self-control and religious orientation to attitude toward premarital relations. Method: This study was correlational. 357 students at Robat Karim Azad University were selected for stratified sampling. Then, they completed the Tangney self-control questionnaire, Allport religious orientation scale and Inventory attitude to Pre-marital relations with the opposite sex. The data were analyzed by Pearson correlation. In this study, all the ethical issues were considered and the authors declared no conflict of interest. Results: The results indicated that there is a significant relationship between self-control and intrinsic religious orientation (r= 0/148), and between self-control and external religious orientation (r= - 0/153), self-control and attitude toward premarital relations (r= -0/107), intrinsic religious orientation and attitude to premarital (r= -0/174), external religious orientation and attitude toward premarital relations (r= 0/197).   Conclusion: Religious orientation and self-control are determining factors in attitude to premarital relationships. It seems that investigating religious orientation and self-control can predict attitudes to premarital relationships. For downloading the full-text of this article please click here.